Positive agenda for developing countries : issues for future trade negotiations (UN New YorkUS, 2000)
Presents papers on the multilateral trade disciplines and other issues such as trade, environment and development; multilateral disciplines on competition; the relationship between anti-dumpiong policy and competition; technology transfer in the WTO agreement and electronic commerce; WTO and developing countries.
Keywords: TRADE AGREEMENTS